Optimum Storage Condition for Spirulina Mat before Applying to Ammonia-Nitrogen Removal from Simulated Shrimp Culturing Water - Chaowanapreecha, Krittayot; Wantawin, Chalermraj; Ruengjitchatchawalya, Marasri (Agriculture and Natural Resources, 2007)
The polyester mats fully attached by Spirulina were stored under different conditions before using for ammonia removal from simulated shrimp culturing water. Three factors on storage were studied; light intensity of 1000, 2000 and 3000 lux; substrate concentration of 1X, 0.5X, 0.3X and 0.1X Zarrouk’s medium; storage time of 2, 4, and 6 weeks. During storage, detachment of excess cells due to growth resulted in accumulation of suspended solids at 6 weeks in the range of 155 to 202 mg/l. More suitable condition for growth during storage yielded more suspended solids in solution. Circulated batch reactor with flow velocity of 0.14 m/s and initial ammonia nitrogen of 1 mg/l was applied for investigating the ammonia removal by stored Spirulina mats. Steady state effluent ammonia concentration of 0.127 mg- N/1 from fresh Spirulina mat reactor (control experiment) was achieved within 20 days. The control relative ammonia removal efficiencies from Spirulina mats, kept six weeks before applying in 1x Zarrouk’s medium under 3000, 2000 and 1000 lux reactor at the end of experiment (25 days), were 93.8%, 92.3% and 91.9%, respectively. While the efficiencies by Spirulina mats, under 1000 lux light intensity, after storing in 0.5x, 0.3x and 0.lx Zarrouk’s medium were 92.0%, 91.8% and 87.9%, respectively. Concentration of daily washed out suspended solid was found stable in all reactors. Optimal condition for storage of Spirulina for long term period (six weeks) was 1000 lux light intensity and 0.1x Zarrouk’s medium.